Muscle oxygenation measured with near-infrared spectroscopy following different intermittent training protocols in a world-class kayaker - a case study - Paulauskas, R.; Nekriošius, R.; Dadeliene, R.; Sousa, A.; Figueira, B. (Sensors, 2022)
Training elite kayakers at a distance of 1000 m is associated with aerobic and anaerobic metabolism, while intermittent training, in a variety of forms, is one of the effective ways to improve cardiorespiratory and metabolic function. Thus, this study aimed to investigate muscle oxygenation responses during repetition training (RT), interval training (IT), and sprint interval training (SIT). Near-infrared spectroscopy (NIRS) monitors were placed on the latissimus dorsi (LD), pectoralis major (PM), and vastus lateralis (VL) of a world-class kayaker during their preparatory period. The intensity of work, relief, and recovery intervals were the independent variables that were manipulated using three different training protocols. The inferential analysis between intermittent training protocols showed significant differences for all variables except total the hemoglobin (tHb) index in LD during bout 2 (F = 2.83, p = 0.1, p2 = 0.205); bout 3 (F = 2.7, p = 0.125, p2 = 0.193); bout 4 (F = 1.8, p = 0.202, p2 = 0.141); and bout 6 (F = 1.1, p = 0.327, p2 = 0.092). During the rest bouts, all training protocols showed significant differences for all variables except muscle oxygen saturation (SmO2) in the VL during bout 5 (F = 4.4, p = 0.053, p2 = 0.286) and tHb in VL during bout 1 (F = 2.28, p = 0.132, p2 = 0.172); bout 2 (F = 0.564, p = 0.561, p2 = 0.049); bout 3 (F = 1.752, p = 0.205, p2 = 0.137); bout 4 (F = 1.216, p = 0.301, p2 = 0.1); and bout 6 (F = 4.146, p = 0.053, p2 = 0.274). The comparison between IT protocols RT and SIT presented similar results. All variables presented higher values during SIT, except HR results. Finally, the comparison between IT and SIT showed significant differences in several variables, and a clear trend was identified. The results of this study suggest that the application of different intermittent exercise protocols promotes distinct and significant changes in the peripheral effect of muscle oxygenation in response to training stimuli and may be internal predictors of hemodynamic and metabolic changes.